Perceptions of the medical relevance of patients` stories of painful and adverse life experiences: a focus group study among Norwegian General Practitioners. Issue 1 (31st December 2022) - Rønneberg, Marianne; Mjølstad, Bente Prytz; Hvas, Lotte; Getz, Linn
ABSTRACT: Purpose: Adverse life experiences increase the risk of health problems. Little is known about General Practitioners' (GPs') thoughts, clinical concepts, and work patterns related to eliciting, including, or excluding their patients' stories of painful and adverse life experiences. We wanted to explore GPs' perceptions of the medical relevance of stories of painful and adverse life experiences, and to focus on what hinders or facilitates working with such stories. Method: Eighteen Norwegian GPs participated in three focus group interviews. The interviews were analysed using reflexive thematic analysis. Results: The participating GPs' views on the clinical relevance of patients' painful and adverse experiences varied considerably. Our analysis revealed two distinct stances: a confident-accepting stance, and an ambivalent-conditional stance . GPs encountered barriers to exploring such stories: scepticism on behalf of the medical discipline; scepticism on behalf of the patients; and, uncertainty regarding how to address stories of painful and adverse experiences in consultations. Work with painful stories was best facilitated when GPs manifested personal openness and prepared availability, within the context of a doctor-patient relationship based on trust. Conclusions: Clearer processes for handling biographical information and life experiences that affect patients' health are needed to facilitate the work of primary care physicians.